Implementing the virtual project management office - Goncalves, Marcus (McGraw-Hill, 2007)
Offers strategies for improvement in virtual project management. This book explores the techniques for improving the outcome of an ePMO design and implementation. It highlights ePMO and details strategies for streamlining communications and interactivity among team members working across barriers of border, culture, and language.